1996
DOI: 10.1135/cccc19961637
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Preparation of 1,3-Bis(dimethylamino)trimethinium Perchlorate, Tetrafluoroborate and Hexafluorophosphate

Abstract: Formylation of ethyl vinyl ether with (chloromethylene)dimethylammonium chloride prepared from dimethylformamide and oxalyl chloride or phosgene followed by successive treatment with dimethylamine and 70% perchloric acid leads to 1,3-bis(dimethylamino)trimethinium perchlorate 1a in high yield. Similarly, work-up of the reaction mixture after formylation with hexafluorophosphoric acid or dimethylamine tetrafluoroborate afforded 1,3-bis(dimethylamino)trimethinium hexafluorophosphate 1b or tetrafluoroborate 1c, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…24 Both the perchlorate and hexafluorophosphate salts of compound 23 were readily synthesized and isolated as light yellow crystals. 25 Screening the counterion, solvent, and concentration revealed that a 15 mM solution of hexafluorophosphate salt 23b in 70% aqueous ethylene glycol possessed a UV spectrum aligned with our needs (Figure 1). To filter light in our flow apparatus, the glycol solution of 23b was pumped through the inner lamp-jacket of the Hanovia apparatus (see the Supporting Information for details) from an external reservoir precooled to −78 °C.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…24 Both the perchlorate and hexafluorophosphate salts of compound 23 were readily synthesized and isolated as light yellow crystals. 25 Screening the counterion, solvent, and concentration revealed that a 15 mM solution of hexafluorophosphate salt 23b in 70% aqueous ethylene glycol possessed a UV spectrum aligned with our needs (Figure 1). To filter light in our flow apparatus, the glycol solution of 23b was pumped through the inner lamp-jacket of the Hanovia apparatus (see the Supporting Information for details) from an external reservoir precooled to −78 °C.…”
Section: ■ Results and Discussionsupporting
confidence: 65%
“…Fortunately, published spectra of vinamidinium perchlorate ( 23a ) suggested it could serve as a solution filter with transmissive character in the region around 240 nm . Both the perchlorate and hexafluorophosphate salts of compound 23 were readily synthesized and isolated as light yellow crystals …”
Section: Resultsmentioning
confidence: 99%
“…It has also to be isolated by crystallization from a viscous solution in aque-ous DMF at -10 to -35°C. Other salts of related vinamidinium cations previously described and used by Arnold and others include tetrafluoroborates, [7][8][9] and hexafluorophosphates. 9…”
Section: Figurementioning
confidence: 99%
“…However, increasing the concentration of the nucleophile by the addition of 1 equiv of KI restored the yield to acceptable levels. The N , N -dimethyl analogue 3c has previously been prepared from propargyl alcohol or ethyl vinyl ether . The 1,4-diazepinium hexafluorophosphate salt 1e (entry 5) was also reduced under these conditions.…”
mentioning
confidence: 99%
“…The N,N-dimethyl analogue 3c has previously been prepared from propargyl alcohol or ethyl vinyl ether. 13 The 1,4-diazepinium hexafluorophosphate salt 1e (entry 5) was also reduced under these conditions.…”
mentioning
confidence: 99%